PREDICTION OF MAIN PARAMETERS OF 24 SOLAR CYCLE - Chumak, O. V. (Одеські астрономічні публікації, 2017)
%B It is shown that there are certain rules which connect a height of previous solar activity cycle with the entropy of the next one. For even and odd cycles these rules are asymmetrical. So if it is known height of the previous cycle one can make estimation for entropy of the next one according to one of these rules. It has been shown also, that entropy (ES) of a cycle has good correlation with its height. On the other hand height of a cycle (Wmax) correlates with duration of its rise branch (Waldmeier’s rule), and it allows to get the estimation of epoch of maximum (Tmax) of future cycle. Epignosis shows that the reliability of such forecasts is about 83%. Below we present the values of main parameters of future 24 cycle obtained according to these rules: Shannon’s entropy ES = 5.0 ± 0.2; height of the cycle Wmax = 95± 20 (in monthly Wolf numbers); duration of arise branch Ta = 4.5 ± 0.5 years; epoch of the cycle maximum Tmax = 2012.25 ± 0.5 year. Full version of the paper is prepared to be published in Solar System Research.